Sources of German unemployment: evidence from a structural VAR model - Tobias Linzert (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2001)
This paper analyzes the dynamic effects of different macroeconomic shocks on unemployment in Germany. In a first step, a cointegration analysis of productivity, prices, real wages, employment, and the unemployment rate reveals two long run relationships, interpreted as a labor demand and a wage setting scheme. Secondly, a structural VAR model is identified using the restrictions suggested by a single macroeconomic model. The impulse response analysis and the forecast error variance decomposition display that price, demand, and labor supply shocks affect unemployment significantly in the short/medium run. Interestingly, however, wage and technology shocks do not seem to play a dominant role.
Keywords: E24; J60; 330; Unemployment; Structural VAR; Cointegration; Arbeitslosigkeit; Arbeitsmarkt; Ökonometrisches Makromodell; VAR-Modell; Schätzung; Preis; Gesamtwirtschaftliche Nachfrage; Arbeitsangebot; Schock; Beschäftigungseffekt; Deutschland